Clonal Exhaustion as a Mechanism to Protect Against Severe Immunopathology and Death from an Overwhelming CD8 T Cell Response - Cornberg, Markus; Kenney, Laurie L.; Chen, Alex T.; Kim, Sung-Kwon; Dienes, Hans P.; Waggoner, Stephen; Welsh, Raymond M.; Selin, Liisa K. (Frontiers in Immunology, 2013)
The balance between protective immunity and immunopathology often determines the fate of the virus-infected host. How rapidly virus is cleared is a function of initial viral load, viral replication rate, and efficiency of the immune response. Here, we demonstrate, with three different inocula of LCMV, how the race between virus replication and T-cell responses can result in different disease outcomes. A low dose of LCMV generated efficient CD8 T effector cells, which cleared the virus with minimal lung and liver pathology. A high dose of LCMV resulted in clonal exhaustion of T cell responses, viral persistence and little immunopathology. An intermediate dose only partially exhausted the T cell responses and resulted in significant mortality, and the surviving mice developed viral persistence and massive immunopathology, including necrosis of the lungs and liver. This suggests that for non-cytopathic viruses like LCMV, HCV and HBV, clonal exhaustion may be a protective mechanism preventing severe immunopathology and death.